PENGARUH LINGKUNGAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR PUSAT PT KERETA API LOGISTIK - Algani, Muhammad Raffi; Akromusyuhada, Akhmad (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This study aims to test and analyze the influence of the Environment and Work Motivation on the Performance of PT Kereta Api Logistik Head Office Employees. The independent variables used are Environment and Work Motivation, while the dependent variable is Performance. The data collection method in this study was carried out by distributing questionnaires to 50 respondents, employees of the PT Kereta Api Logistik Head Office. The research method used is a quantitative method that is associative in nature using primary data. These results show that the environment has a positive and significant effect on employee performance with a t-count value greater than t-table 3,617 2,01 and a significant value of 0,001 0,05, work motivation has a positive and significant effect on employee performance with a t-count value greater from the t-table 2,226 2,01 and a significant value of 0,031 0,05. Together the environment and work motivation have a significant effect on employee performance with a calculated F value greater than F table 25,826 3,20 and a significant value of 0,000 0,05.Keywords: Work Environment, Motivation, Employee Performance